2023
DOI: 10.3390/ijms24054631
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells in Kidney Ischemia: From Inflammation and Fibrosis to Renal Tissue Regeneration

Abstract: Ischemic nephropathy consists of progressive renal function loss due to renal hypoxia, inflammation, microvascular rarefaction, and fibrosis. We provide a literature review focused on kidney hypoperfusion-dependent inflammation and its influence on renal tissue’s ability to self-regenerate. Moreover, an overview of the advances in regenerative therapy with mesenchymal stem cell (MSC) infusion is provided. Based on our search, we can point out the following conclusions: 1. endovascular reperfusion is the gold-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 104 publications
1
9
0
Order By: Relevance
“…In such transplant patients, the protection of allograft function is particularly crucial, especially in renal fibrosis after IRI. MSCs can respond to specific triggers with differentiation to mature cells with consequent tissue regeneration [ 23 ]. MSCs could represent a revolutionary treatment for patients with fibrotic evolution.…”
Section: Discussionmentioning
confidence: 99%
“…In such transplant patients, the protection of allograft function is particularly crucial, especially in renal fibrosis after IRI. MSCs can respond to specific triggers with differentiation to mature cells with consequent tissue regeneration [ 23 ]. MSCs could represent a revolutionary treatment for patients with fibrotic evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Cianci et al [47] have recently published original data on NGAL and circulating renal stem cell (RSC) changes before and after PTRA and stenting in five patients with RAS.…”
Section: The Role Of Blood Ngal (Neutrophil Gelatinase-associatedmentioning
confidence: 99%
“…MSCs ability to migrate and/or differentiate in the kidney following several renal insulting mechanisms defines the extraordinary repairing potentiality of these peculiar cells. Once migrated or activated in the damaged kidney, MSCs produce and release, through extracellular vesicles and exosomes, a variety of cytokines and chemokines able to reduce inflammation and increase different reparative pathways[47] [58]. Some reports in animal models have explored the potential restorative role of stem cells after renal reperfusion and have demonstrated encouraging and promising results[59] [60].…”
mentioning
confidence: 99%
“…The main producers of MCP-1 are monocytes and macrophages, although it is also expressed by various other cell types such as endothelial cells, fibroblasts, epithelial cells, smooth muscle cells, mesangial cells, astrocytes, and microglia ( 4 , 5 ). Upon binding to its receptor, MCP-1 can induce homing, migration, activation, differentiation,and development of lymphocytes and NK cells; facilitate infiltration of monocytes and macrophages; promote inflammation occurrence; stimulate angiogenesis; as well as exert fibrotic effects ( 6 ). Studies have demonstrated that MCP-1 plays a significant role in fibrosis affecting multiple organs ( 7 ).…”
Section: Introductionmentioning
confidence: 99%